Finnishness, Whiteness and Coloniality - Hoegaerts, Josephine; Liimatainen, Tuire; Hekanaho, Laura; Peterson, Elizabeth (Helsinki University Press, 2022)
This multidisciplinary volume reflects the shifting experiences and framings of Finnishness and its relation to race and coloniality. The authors centre their investigations on whiteness and unravel the cultural myth of a normative Finnish (white) ethnicity. Rather than presenting a unified definition for whiteness, the book gives space to the different understandings and analyses of its authors. This collection of case-studies illuminates how Indigenous and ethnic minorities have participated in defining notions of Finnishness, how historical and recent processes of migration have challenged the traditional conceptualisations of the nation-state and its population, and how imperial relationships have contributed to a complex set of discourses on Finnish compliance and identity. With an aim to question and problematise what may seem self-evident aspects of Finnish life and Finnishness, expert voices join together to offer (counter) perspectives on how Finnishness is constructed and perceived. Scholars from cultural studies, history, sociology, linguistics, genetics, among others, address four main topics: 1) Imaginations of Finnishness, including perceived physical characteristics of Finnish people; 2) Constructions of whiteness, entailing studies of those who do and do not pass as white; 3) Representations of belonging and exclusion, making up of accounts of perceptions of what it means to be 'Finnish'; and 4) Imperialism and colonisation, including what might be considered uncomfortable or even surprising accounts of inclusion and exclusion in the Finnish context. This volume takes a first step in opening up a complex set of realities that define Finland's changing role in the world and as a home to diverse populations.